If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -9n + -17 = 0 Reorder the terms: 7 + -17 + -9n = 0 Combine like terms: 7 + -17 = -10 -10 + -9n = 0 Solving -10 + -9n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -9n = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -9n = 0 + 10 -9n = 0 + 10 Combine like terms: 0 + 10 = 10 -9n = 10 Divide each side by '-9'. n = -1.111111111 Simplifying n = -1.111111111
| (.5)(x)(x-3)=20 | | 1.3x-6= | | 5x+14=-56-5x | | x+31+61=5x-22 | | 1x/4=8(x-3) | | -3p-4+4p+8=x | | r+10=22 | | 2b-10=b | | 25x+15y=305 | | 9x+11x=180 | | B=2b-10 | | 5abcdefg=6abcdefg-2a+3b | | 10x^3+2y=0 | | 12x+2x=7 | | 0=64x^2-36 | | 2x+y=X | | 6x+9=4x-7 | | a(abc)= | | 63=x-27 | | 7x+16y=11 | | x+37=91 | | (3b-6)+(4b-6b+10)= | | p+(2p+15)+(p+15)=360 | | 16x^2+9=5 | | .15+.2m=.55 | | 1+4v+6v=-19 | | 6*[5*(3*3*3-17)]= | | 3w-9=36 | | 3(y+7)=4(y-7) | | (2y-1)(2y+4y-3)= | | x-6=89 | | 6In(3x)=8 |